2008
DOI: 10.1056/nejmoa0802878
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Disoproxil Fumarate versus Adefovir Dipivoxil for Chronic Hepatitis B

Abstract: Among patients with chronic HBV infection, tenofovir DF at a daily dose of 300 mg had superior antiviral efficacy with a similar safety profile as compared with adefovir dipivoxil at a daily dose of 10 mg through week 48. (ClinicalTrials.gov numbers, NCT00116805 and NCT00117676.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

45
975
17
39

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,089 publications
(1,076 citation statements)
references
References 37 publications
45
975
17
39
Order By: Relevance
“…Viral suppression occurred in HBeAg-negative patients receiving ADV for 48 weeks was 63% with no amino acid substitutions within the HBV DNA polymerase associated with phenotypic resistance [22]. These data show that for HBeAg-negative CHB patients, de novo combination treatment of LAM ?…”
Section: Discussionmentioning
confidence: 73%
“…Viral suppression occurred in HBeAg-negative patients receiving ADV for 48 weeks was 63% with no amino acid substitutions within the HBV DNA polymerase associated with phenotypic resistance [22]. These data show that for HBeAg-negative CHB patients, de novo combination treatment of LAM ?…”
Section: Discussionmentioning
confidence: 73%
“…Tenofovir disoproxil fumarate (TDF) is a highly potent drug active against a broad spectrum of viral infections, including human immunodeficiency virus (HIV-1) and HBV [8]. Recently, its high potency and lasting antiviral effect were confirmed by two randomized trials, mostly in treatment-naive HBV monoinfected, HBeAg-positive, and HBeAg-negative patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…The registration trials for TDF required a estimated glomerular filtration rate (eGFR) [70 ml/min, absence of anemia, neutropenia, and liver decompensation or presence of unstable comorbidities [3]. In practice, patient complexity can be greater, comorbidities not always optimized, and adherence less assured.…”
mentioning
confidence: 99%
“…For most clinicians, peginterferon is infrequently considered due to the greater complexity of monitoring, higher frequency of adverse effects and patient preference, which narrows the treatment options to TDF or entecavir. In the registration trials of treatment-naïve patients with chronic hepatitis B, both TDF and entecavir demonstrated high rates of on-treatment HBV DNA suppression and low rates of viral resistance coupled with excellent safety [3,4]. Given that TDF and entecavir have been approved therapies for HBV for more than a decade, data derived from ''real-world'' cohort studies have helped fill knowledge gaps regarding the use of these drugs in clinical practice.…”
mentioning
confidence: 99%